IMPLEMENTASI KEBIJAKAN PERLINDUNGAN ANAK BERHADAPAN DENGAN HUKUM DI LAPAS KABUPATEN KLATEN - Puji Astutik; Dewi Rostyaningsih; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Children are nation seed thus children rights must be protected like children in conflict with law. Problem usually faced by children in conflict with the law is a child must be placed with adult prisoner. The purpose of this research is to get visible image from realization of protection of children in conflict with the law at Klaten Region Prison. Method used in this research is qualitative by using Mazmanian and Sabatier theory. The result of this research is that the implementation of policy of protection of children in conflict with the law at Klaten Region Prison is not optimize yet because of within implementation of policy of protection of children in conflict with the law at Klaten Region Prison still face some problems like the lack of information access, education and teaching. Suggestion from the researcher is to review giving alternative assistance to children in conflict with law who is late in signing up as kejar paket C participant. Revering back cooperation agreement among prison and education institution in relation with education service. Socializing about the existence of children in conflict with law in IIb class prison so that assistance which is given do not have common characteristic.